2020
DOI: 10.1371/journal.pone.0241299
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p120ctn causes EGFR-targeted therapy resistance and failure

Abstract: Epidermal growth factor receptor (EGFR) plays a vital role in cell division and survival signaling pathways. EGFR is activated in nearly every cancer type, and its high expression in tumors is correlated with poor patient outcome. Altogether, EGFR is a prime candidate as a therapeutic target. While targeted EGFR therapy is initially effective in 75% of patients, a majority of patients relapse within the first year due to poorly understood mechanisms of resistance. p120-catenin (p120ctn) has recently been impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In mice treated with DBPDE we found that diet containing 5% BRB resulted in a significant reduction of tumor formation [ 15 ]. Given that p120ctn can alter EGFR therapy in HNSCC [ 10 ] and, as shown in Fig 1 , p120ctn is downregulated following DBPDE treatment, we set out to determine if BRB treatment altered p120ctn expression in DBPDE-induced tumors. Oral cavity tissue was previously harvested from DBPDE treated mice with and without BRB administration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In mice treated with DBPDE we found that diet containing 5% BRB resulted in a significant reduction of tumor formation [ 15 ]. Given that p120ctn can alter EGFR therapy in HNSCC [ 10 ] and, as shown in Fig 1 , p120ctn is downregulated following DBPDE treatment, we set out to determine if BRB treatment altered p120ctn expression in DBPDE-induced tumors. Oral cavity tissue was previously harvested from DBPDE treated mice with and without BRB administration.…”
Section: Resultsmentioning
confidence: 99%
“…Because we have previously shown that decreased p120ctn expression causes EGFR therapy resistance [ 10 ], we wanted to determine EGFR expression levels in DBPDE treated tumors and whether BRB treatment altered its expression. In normal epithelium, EGFR is strongly expressed in the basal layers, and expression decreases as the epithelium differentiates and migrates toward the superficial layers ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR is widely expressed in nearly every cancer type, and its high expression in tumors correlates with poor patient out-come [16]. Several studies have demonstrated that patients with digestive tumors benefited from EGFR-targeted therapy using cetuximab [17][18][19].…”
Section: Discussionmentioning
confidence: 99%